STUDY OF THE PHYSICAL DEVELOPMENT, PHYSICAL AND TECHNICALTACTICAL PREPAREDNESS OF WOMEN BASKETBALL PLAYERS - J. Tzankova (Trakia Journal of Sciences)
The sporting achievement in basketball is greatly influenced by both morphofunctional indicators and the level of development of special physical qualities in combination with technical and tactical training. The aim of the study is to improve the training process in adolescent basketball players, through analysis and evaluation of physical development, physical and technical; and tactical training. The methoud used is testing. A test battery include 15 indicatorswas used. The methouds of theoretical research, anthropometry and sports-pedagogical testing are applied in the article. The results of the study are processed mathematically and statistically through variation analysis, body mass index, correlation and comparative analysis. In analysis of the results in 6 of the indicators, the adolescent basketball players from the surveyed team have reached grades above the average level. In conclusion there is a need to improve the ability to lead the ball at high speed, shooting in motion over time and the use of various means to develop the abdominal muscles.